2020
DOI: 10.17582/journal.pjz/20190825090821
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Substituting Soybean Meal with Moringa oleifera Meal on the Growth and Body Composition of Labeo rohita Fingerlings

Abstract: The present study was conducted to examine the effect of replacing soybean meal in fish diets with the cheaper alternative plant protein moringa meal (Moringa oleifera) on growth and body composition of Labeo rohita fingerlings. L. rohita (average weight 190.25±00g) were stocked randomly in glass aquaria for a 90 day feeding trial. Fish were fed twice daily with four different iso-nitrogenous diets at a feeding level of 3% of total biomass. The diets contained 26% crude protein in which moringa meal substitute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…In Labeo rohita, body composition could be unaffected by the substitution of moringa leaves for soybean meal as a cost-effective source of high-quality plant protein (Masood et al, 2020). This statement has been supported by the findings of Arsalan et al (2016), who demonstrated that fishmeal could be supplemented with moringa leaf meal up to 10% to boost the nutritional value of L. rohita fingerlings.…”
Section: Use Of Moringa Leaves In Aquaculturementioning
confidence: 77%
“…In Labeo rohita, body composition could be unaffected by the substitution of moringa leaves for soybean meal as a cost-effective source of high-quality plant protein (Masood et al, 2020). This statement has been supported by the findings of Arsalan et al (2016), who demonstrated that fishmeal could be supplemented with moringa leaf meal up to 10% to boost the nutritional value of L. rohita fingerlings.…”
Section: Use Of Moringa Leaves In Aquaculturementioning
confidence: 77%
“…Using Aspergillus niger during fermentation is one method for reducing the content of crude and neutralize antinutritional substances in moringa leaves. A. niger produces enzymes such as protease, amylase and cellulase that aid in improving the digestibility of feeds [15]. The addition of A. niger in the fermentation process is expected to enhance the nutritional value of moringa leave meal so that it can be utilized as an alternative raw material for the production of fish feed.…”
Section: Introductionmentioning
confidence: 99%